PENGARUH PERSEPSI DAN PEMAHAMAN MAHASISWA TERHADAP KESIAPAN KERJA LULUSAN PERGURUAN TINGGI DALAM MENGAHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - Felicia Santoso (Ma Chung Press, 2015)
ASEAN Economic Community (AEC) will be implemented at the end of 2015, where in AEC there will be a free market which occurred in all ASEAN countries member. With the existence of AEC, the competition to get a job will be tighter, and it needs more skills from every college graduates so they can compete it. By knowing the students’ perceptions about AEC and understanding about AEC, the college graduates are expected to be ready to enter the job world while AEC occur. The purpose of this research is to know the students’ perception and understanding about AEC which influence the significant of work readiness for college graduates to confront ASEAN Economic Community (AEC). This research use quantitative descriptive methods and the data sources of this research is primary data. Primary data of this research is obtained from questionnarie which is filled by the students of some universities in the Malang city from economics and business faculty. The sample technique is using nonprobability sampling method with purposive sampling method. The data analysis technique which used in this research is GSCA. The first results of this research is students’ perception do not affect of work readiness college graduates significantly to confront ASEAN Economic Community (AEC). The second results of this research is an understanding of AEC which influence college graduates of work readiness significantly to confront ASEAN Economic Community (AEC).